2017
DOI: 10.3390/socsci6020063
|View full text |Cite
|
Sign up to set email alerts
|

A Process Review of the Indashyikirwa Couples Curriculum to Prevent Intimate Partner Violence and Support Healthy, Equitable Relationships in Rwanda

Abstract: Indashyikirwa is a Rwandan intimate partner violence (IPV) prevention program being implemented by CARE International Rwanda, Rwanda Women's Network (RWN), and Rwanda Men's Resource Centre (RWAMREC). A central aspect of the programme is a 20-session curriculum for heterosexual couples designed to support healthy, non-violent relationships. This paper draws on qualitative interviews with 15 couples (before and after the curriculum) and 9 field staff to assess couples' impressions, comprehension of, and engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…The programme, known as Indashyikirwa ("Agents of Change" in Kinyarwanda, trial identifier: NCT03477877), was implemented by CARE International, Rwanda; the Rwanda Women' s Network (RWN); and the Rwanda Men' s Resource Centre (RWAMREC) between 2015 and 2018, with funding from the Rwandan office of the Department for International Development (DFID-R). The full Indashyikirwa program included four interlocking components: a 21-session couples' curriculum; community outreach by trained community activists; the creation of an enabling environment through training and active involvement of key opinion leaders; and provision of support to victims through the creation of women' s "safe spaces" [13,14].…”
Section: Viewpoints Research Theme 1: Countdown Coveragementioning
confidence: 99%
See 3 more Smart Citations
“…The programme, known as Indashyikirwa ("Agents of Change" in Kinyarwanda, trial identifier: NCT03477877), was implemented by CARE International, Rwanda; the Rwanda Women' s Network (RWN); and the Rwanda Men' s Resource Centre (RWAMREC) between 2015 and 2018, with funding from the Rwandan office of the Department for International Development (DFID-R). The full Indashyikirwa program included four interlocking components: a 21-session couples' curriculum; community outreach by trained community activists; the creation of an enabling environment through training and active involvement of key opinion leaders; and provision of support to victims through the creation of women' s "safe spaces" [13,14].…”
Section: Viewpoints Research Theme 1: Countdown Coveragementioning
confidence: 99%
“…The findings reported herein derive from two repeat cross-sectional surveys of community members, conducted as part of a larger community randomised trial, with qualitative data from a nested process evaluation [15]. A separate manuscript reports on the impact that the couple' s curriculum had on relationship dynamics and IPV levels among couples who participated in the programme' s 5-month couples' curriculum (for more details on the couple' s curriculum, see [13]). Longitudinal evaluation of the couples' programme demonstrated that couples who participated in the training reported less physical, sexual, emotional, and economic IPV; improved relationship quality; better communication; improved conflict management; fewer depressive symptoms; better oveall health; and attitudes less supportive of wife beating, than did control couples at 12 and 24 months followup [16].…”
Section: Viewpoints Research Theme 1: Countdown Coveragementioning
confidence: 99%
See 2 more Smart Citations
“…A range of studies, including longitudinal studies, have found that women experiencing emotional IPV are more likely to experience adverse mental health outcomes, including depression and suicidal ideation [4,5]. An analysis of data from young women (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) in South Africa [4] found that a range of potential measures of emotional IPV showed a consistent positive association with higher depression scores and suicidal ideation. Other studies have shown that women's experience of emotional IPV is associated with psychosomatic conditions (such as nervous twitching, cramps and paralysis, and dizziness) [6] as well as fear, anxiety, reduced social support, and compromised self-esteem [7].…”
Section: Introductionmentioning
confidence: 99%